2014
DOI: 10.1371/journal.pone.0100011
|View full text |Cite
|
Sign up to set email alerts
|

Serum Progesterone Elevation Adversely Affects Cumulative Live Birth Rate in Different Ovarian Responders during In Vitro Fertilization and Embryo Transfer: A Large Retrospective Study

Abstract: In order to explore the relationship between serum progesterone (P) level on the day of human chorionic gonadotrophin (HCG) administration and cumulative live birth rate in patients with different ovarian response during in vitro fertilization (IVF), we carried out this retrospective cohort study including a total of 4,651 patients undergoing their first IVF cycles from January 2011 to December 2012. All patients with a final live birth outcome (4,332 patients) were divided into three groups according to ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 22 publications
3
59
0
2
Order By: Relevance
“…Our results thus extend the observation of two recent studies focused on Day 3 embryos [1516] and deserve further research.…”
Section: Resultssupporting
confidence: 89%
“…Our results thus extend the observation of two recent studies focused on Day 3 embryos [1516] and deserve further research.…”
Section: Resultssupporting
confidence: 89%
“…Interestingly, parallel research has also shown that high serum P4 at trigger has a positive or direct correlation on the number of oocytes retrieved, without an obvious effect on quality [3, 6, Fig. 2 Receiver operator characteristic curve for live birth and ongoing pregnancy rate when compared to any negative %ΔP4 with AUC 0.692 [15][16][17]. A study of the cumulative effects of fresh and FET cycles has shown that elevated serum P4, previously repeatedly reported to have a negative impact on LBR, may actually depend on ovarian response [15].…”
Section: Discussionmentioning
confidence: 99%
“…The lower clinical pregnancy and live birth rates in group with high basal or late follicular progesterone may be explained by its effect on endometrium (altered receptivity) or its effect on oocyte/embryo quality or the synchrony between the two (advancement of implantation window)[19].The present literature presents conflicting evidence on its effect on oocyte and embryo quality. While some studies demonstrated an adverse effect on oocyte and top quality embryos rates[20] [21][22] [23], others showed comparable oocyte quality, fertilization, cleavage rates and embryo quality between high and normal progesterone groups[9] [24]-[29]. When it comes to clinical pregnancy and live birth rates, the dilemma continues.…”
mentioning
confidence: 99%